Dynamics of the Role of PAI Teachers in Forming Religious Culture and Religious Discipline in Students - Khomisah; Leksono, Aris Adi; Nur Kholis, Mohammad Maulana (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2023)
This research explores the role of Islamic Religious Education teachers in forming religious culture in the school environment. This research collects data through interviews, observation, and documentation using qualitative methods and a case study approach. The research results show that Islamic Religious Education teachers are crucial as students' mentors, models, and advisors. They help internalize and encourage the practice of religious values ​​in students' daily lives. Schools also create this religious culture by establishing regulations, work programs, facilities, and regular religious activities. A solid religious culture in schools can shape positive character in students and create a conducive learning environment, potentially improving education quality. However, research also identifies several challenges, such as lack of support, limited resources, and negative influences from the surrounding environment that can affect the effectiveness of these efforts. Therefore, increasing support and problem-solving for these obstacles is needed to strengthen the role of Islamic Religious Education teachers in forming religious culture in schools.